Self-Responsibility of the "Active Social Citizen": Different Types of the Policy Concept of "Active Social Citizenship" in Different Types of Welfare States. (January 2019) - Eggers, Thurid; Grages, Christopher; Pfau-Effinger, Birgit
The article aims to answer the following research questions: (a) How far do European welfare states differ in the use of the policy concept of the active social citizen? and (b) How far is it possible to explain the differences with welfare regime types and welfare culture? The article distinguishes between two different types of the policy concept of active social citizenship with regard to self-responsibility. It argues that the active social citizen's self-responsibility could be underpinned either by a major role of the welfare state, which promotes the citizens' self-determination, or by a minor role of the state, which forces citizens to be self-reliant for funding and for organizing their own social security and services. The article is based on a cross-national comparative study for two policy fields (unemployment and long-term care policies for older people) in three welfare states (Denmark, England, and Germany), and analyzes legal frameworks, data from MISSOC (Mutual Information System on Social Protection) and secondary literature. The comparative analysis shows that countries differ in the type of the policy concept of active social citizenship they use. Differences in the type of welfare regime and also differences in the welfare culture contribute to an explanation of these differences. The article is innovative in that it offers a systematic analysis of the differences in the ways in which welfare states of different regime types conceptualize "active social citizenship" with regard to the citizens' self-responsibility.